Taxonomy and Molecular Phylogeny of Three Species of Scuticociliates From China: Citrithrix smalli gen. nov., sp. nov., Homalogastra binucleata sp. nov. and Uronema orientalis Pan et al., 2015 (Protozoa, Ciliophora, Oligohymenophorea), With the Proposal of a New Family, Citrithrixidae fam. nov. - Liu, Mingjian; Wang, Chundi; Hu, Xiaozhong; Qu, Zhishuai; Jiang, Limin; Al-Farraj, Saleh A.; El-Serehy, Hamed A.; Warren, Alan; Song, Weibo (Frontiers in Marine Science, 2020)
The morphology and taxonomy of three scuticociliates found in China, viz. Citrithrix smalli sp. nov., Homalogastra binucleata sp. nov., and Uronema orientalis Pan et al., 2015, were investigated. The small subunit ribosomal RNA (SSU rRNA) gene of these species, and the cytochrome c oxidase subunit I (COI) gene of Uronema orientalis, were sequenced and compared with those of related taxa to determine their systematic positions. The new monotypic genus Citrithrix gen. nov. is characterized by its lemon-shaped body, posteriorly located cytostome, dominant oral groove, and the compact structure of its multi-rowed membranelles 1 and 2 (M1, M2). Based on both morphological and molecular data, this new genus cannot be assigned to any known family and thus, a new family, Citrithrixidae fam. nov., is proposed within the order Philasterida. Homalogastra binucleata sp. nov., a brackish water form (salinity 2‰), differs from all congeners in having two macronuclear nodules. Uronema orientalis closely resembles the type population in all respects other than having fewer somatic kineties.